French patisserie master recipes and techniques from the ferrandi school of culinary Arts - Ferrandi School of Culinary Arts; Nurra, Rina; Adedotun, Helen; Abramowitz-Moreau, Carmella; Evans, Ansley; Walsh, Caitilin; Doux, Rachel (Paris Flammarion, 2017)
"Ferrandi, the French School of Culinary Arts in Paris--dubbed -the Harvard of gastronomy- by Le Monde newspaper--is the ultimate pastry-making reference. From flaky croissants to paper-thin mille-feuille, and from the chestnut cream-filled Paris-Brest to festive yule logs, this comprehensive book leads aspiring pastry chefs through every step--from basic techniques to Michelin-level desserts. Featuring advice on how to equip your kitchen, and the essential doughs, fillings, and decorations, the book covers everything from quick desserts to holiday specialties and from ice creams and sorbets to chocolates. Ferrandi, an internationally renowned professional culinary school, offers an intensive course in the art of French pastry making. Written by the school's experienced teaching team of master patissiers and adapted for the home chef, this fully illustrated cookbook provides all of the fundamental techniques and recipes that form the building blocks of the illustrious French dessert tradition, explained step by step in text and images. Practical information is presented in tables, diagrams, and sidebars for handy reference. Easy-to-follow recipes are graded for level of difficulty, allowing readers to develop their skills over time. Whether you are an amateur home chef or an experienced patissier, this patisserie bible provides everything you need to master French pastry making."-- Provided by publisher.
Equipment -- Basic techniques -- Ingredients -- Pastries -- Creams -- Sponge & meringue layers -- Meringues -- Macarons -- Simple cakes & desserts -- Entremets: layered desserts & gâteaux -- Festive occasions -- Candies, confections & jams -- Chocolate -- Decorations -- Frozen desserts.
Simultaneously published in French as: Pâtisserie : Toutes les techniques et recettes dʹune eʹcole dʹexcellence, ©Flammarion, S.A. Paris, 2017.
Keywords: Cooking -- France; Desserts -- France; Pastry -- France